Industrialisation and the Big Push in a Global Economy - Jens Wrona; Udo Kreickemeier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Is it possible to escape from a poverty trap through international trade? To answer this question, we extend Murphy et al.'s (1989b) famous “Big Push” model towards a global economy. In general oligopolistic equilibrium, firms choice between a traditional CRS and a modern IRS technology results in three different equilibria, featuring no, incomplete, or complete industrialisation across a continuum of sectors. With labour being sufficiently scarce, multiple equilibria exist, and the economy may end up trapped in an incompletely industrialised low-welfare equilibrium as firms fail to coordinate their technology choices. Since the adoption of the modern technology is impeded by tougher competition through international trade, the vicious circle of poverty is aggravated by the forces of globalisation.
Keywords: F12; O14; F43; 330